Assessment of mitochondrial toxicity in newborns and infants with congenital cytomegalovirus infection treated with valganciclovir. Issue 7 (14th March 2022) - Ortiz-Gracia, Alba; Ríos, María; Tobías, Ester; Noguera-Julian, Antoni; García-García, Francesc Josep; Cantó-Santos, Judith; Valls-Roca, Laura; Garrabou, Glòria; Grau, Josep Maria; Cardellach, Francesc; Sánchez, Emilia; Morén, Constanza; et al.
Abstract : Background: Ganciclovir/valganciclovir is currently indicated during the first 6 months of life in symptomatic children with congenital cytomegalovirus (CMV) infection. However, this treatment may have the potential to induce mitochondrial toxicity due to off-target inhibition of DNA-polymerases. Similar anti-HIV drugs have been associated with mitochondrial toxicity but this has never been explored in CMV. Objective: To determine the potential mitochondrial toxicity profile at the genetic, functional and biogenesis level in peripheral blood mononuclear cells from a cohort of newborns and infants with symptomatic congenital CMV infection (treated with valganciclovir, untreated and uninfected controls). Design: Longitudinal, observational and controlled study. Setting and patients: Subjects were recruited at the tertiary referral Hospital Sant Joan de Déu and experiments were conducted at IDIBAPS-Hospital Clínic of Barcelona, Spain. CMV-infected newborns underwent comprehensive monthly clinical follow-up. Methods: Mitochondrial parameters, audiometry and neurological assessment were measured at baseline, 3–6 and 12 months after inclusion in the study. The Kruskal-Wallis test for k-independent samples and Friedman tests for repeated measurements were applied. Results: Complex IV, citrate synthase enzymatic activities and mtDNA remained preserved in congenital CMV-infected infants treated with valganciclovir compared with controls (p>0.05 in all cases). Conclusions: No evidence of mitochondrial toxicity was found in infants treated with valganciclovir for congenital CMV. Abstract : Some antivirals are associated with mitochondrial toxicity due to off-target inhibition of DNA-polymerases. This study looks for evidence of mitochondrial toxicity in infants with congenital CMV infection, treated with valganciclovir. In a series of experiments no evidence of mitochondrial toxicity was found.